PENGARUH PELATIHAN TERHADAP PENDAPATAN INDIVIDU: STUDI KASUS WIRAUSAHA WANITA INDONESIA - Musthafa, Imelfina; Ridwan, Endrizal (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
This study aims to analyze the effect of training attended by female entrepreneurs in the last three years on individual income using Sakernas 2021 data. This study uses Propensity Score Matching (PSM) to achieve the research objectives. The results show that the probability of training is influenced by age, education, marital status, and being registered in the licensing system. The study found that training reduces women's entrepreneurial income by 16.3%. The training conducted by women entrepreneurs has not been applied in business activities so that this training has not had a significant impact on income.